'On the Horns of a Dilemma'! Climate Change, Forest Conservation and the Marginal People in Indian Sundarbans. Issue 2 (3rd May 2020) - Roy, Dayabati
Abstract: The marginal people of the Indian part of Sunderbans (SDB) do now subsist 'between two fires' – climate change and climate change adaptation and mitigation policies. They have already felt the fire of climate change in terms of loss of livelihoods, homelessness, and even life harm. They have begun recently to experience the fire of climate change adaptation and mitigation policies. The fallout of this situation, thus, comes in form of mass-exodus, and social and political conflicts at the margin. This article tells a story of how the postcolonial government in India, like its predecessor i.e. the British colonialists, would orchestrate a concerted effort in accumulation-based development in the name of conservation of SDB. Critically engaging the trajectory of policy interventions including the Forest (Conservation) Act, 1980, the Draft National Forest Policy, 2018 and the Scheduled Tribes and other traditional forest dwellers (Recognition of forest rights) act, 2006, it explores the dynamic way in which the government uses the climate change and conservation excuse to evict the Scheduled Tribes and other traditional forest dwellers from the forestlands. In conclusion, this article argues why we should go beyond the capitalist 'growth' narrative in order to formulate a more grounded climate and social justice legislation.